The Contribution of Leadership Behaviour to the Performance of Selected Ethiopian Sports Federations - Samson Wondirad; Tesfay Asgedom; Aschenaki Taddese (Indonesian Journal of Sport Management, 2023)
The purpose of this study was to investigate the relationship between leadership behaviour and performance of selected Ethiopian sports federations. The researcher used a mixed-methods sequential explanatory design. The population of the study from sport federations employee aimed to fill questionnaire was (N = 126) and selected using availability sampling technique. Leaders from both federation for the purpose of interview was (N = 6) selected using snowball sampling technique. The quantitative data analysis was processed using IBM SPSS Amos 23.0 software. Structural equation modelling (SEM) has been used to study this relationship. Confirmatory Factory Analysis (CFA) was used to test the hypothesis between leadership behaviour and performance observed variables and their underlying latent constructs exist. The finding of study found that there was a positive correlation between leadership behaviour and performance of selected sport federations. The Selected Ethiopian Sports Federations was recommended to provide the performance appraisal of their employees that aimed to improve the organization performance.